Misleading Memes. The Effects of Deceptive Visuals of the British National Party - Ofra Klein (Coordinamento SIBA, 2020)
This study investigates how visual manipulation is employed on the Facebook page of a far-right party; and whether manipulation evokes different forms of engagement from Facebook users. The study takes as a case the Facebook page of the British National Party (BNP), which has recently been censored from the social media platform. It therefore provides a rare insight in the visual practices of the party's online political communication. A manual coding of 342 images into factual, funny, fallacious or fabricated content finds that completely fabricated information in images is rare. However, most images do contain information that is presented in a fallacious or misleading manner. The results show how deliberate manipulated images evoke more engagement in the form of comments and more negative emotional responses than images that present information in a factual or funny manner.